GBDKVA score: a scoring system for preoperative risk assessment of adrenal tumors ≤6cm - Yang, Siwei; Yang, Xianrui; Yao, Zhili; Guo, Qi; Hou, Zekai; Wang, Chenyu; Cui, Ronghao; Wang, Zhun; Li, Gang; Quan, Changyi; Niu, Yuanjie; Zhao, Yan; et al. (Frontiers in Endocrinology, 2025)
ObjectivesTo propose a comprehensive scoring system for adrenal tumors ≤ 6cm and evaluate its rationality and validity.Materials and methodsThis study retrospectively analyzed 268 patients with primary adrenal tumors who underwent laparoscopic surgery from January 2018 to December 2022 and all of them met the inclusion criteria. Evaluation scores were calculated for gender (G), body mass index (BMI) (B), tumor diameter (D), the relative position of the tumor to the kidney (K), the relative position of the tumor and the blood vessels (V) and the tumor location in the adrenal gland (A). Then, the total scores were correlated with the operation results, so as to verify the feasibility of GBDKVA in evaluating the surgical risk.ResultsThe GBDKVA score showed a consistent and statistically significant correlation with operation time (OT) and blood loss (BL), as well as a correlation with postoperative complications in patients (p < 0.01), but no significant correlation was found with recovery time of gastrointestinal function, bed rest days, indwelling drainage tube days and postoperative hospitalization time were opposite.ConclusionsGBDKVA score is reliable for preoperative risk assessment of patients with adrenal tumors ≤6cm.